Análisis crítico propositivo de la comunicación institucional interna vinculada con el accionar del Gobierno Provincial de Loja, período julio 2011-enero 2012. Lineamientos alternativos - Rojas Carrión, María Fernanda (2015)
The thesis "purposeful Critical analysis of internal corporate communication linked to the actions of the Provincial Government of Loja, period July 2011 -January 2012. Alternative Guidelines" of the need to improve communication internally in the organization, determining that interference level is in the normal development of labor relations, and thereby create and expand communication processes to achieve organizational efficiency. This work got to know the strengths and weaknesses that owns the Provincial Government of Loja represented in authorities servers and workers; synthetic scientific and analytical method was used. Likewise the techniques of observation, survey and interviews were used to verify the objectives and hypotheses of the research. With conclusions and recommendations, it was found that the degree of satisfaction of staff working in the provincial body is medium, the lack of clear strategies for internal communication, lack of institutional goals and objectives, there is no willingness to recognize and troubleshoot communication by the representative of authority, there is the staff's willingness to be part of a process to improve communication within the organization, there is no internal corporate communication plan that allows the creation and maintenance of good relations between its members. The proposal contains different elements that help strengthen and improve the levels of communication and sense of belonging to the provincial agency, some of the alternatives included in the proposal were established by the welcome they have in the medium under study.